The Application Potential of the Raw Goat Milk-Derived Strain Lactococcus lactis MK 1/3 for the Dairy Industry - Andrea Lauková; Martin Tomáška; Maroš Drončovský; Rastislav Mucha; Emília Dvorožňáková; Miroslav Kološta; Monika Pogány Simonová (Applied Sciences, 2025)
Raw goat milk-derived Lactococcus lactis MK1/3 (CCM 9209) was studied to show its potential for use in the dairy industry. Finding an innovative strain indicates having a new safe, original additive for functional food. The strain has been shown to be safe using a model experiment with Balb/c mice, when no mortality was noted. Its counts were increased continually during 120 days, with the highest value on day 90 (4.38 ± 1.24 colony-forming unit per gram (CFU/g, log 10). In vivo (in the experimental mice), anti-staphylococcal effect was noted with difference 1.82 log cycles. The safety of the strain MK1/3 has been also indicated by the fact that it did not produce damaging enzymes, it has been susceptible to antibiotics, and it has shown low-grade biofilm-forming ability (0.126 ± 0.35). This strain has tolerated bile, and low pH sufficiently. It produced a postbiotic active substance with inhibitory activity against cheese and milk contaminants (Enterococci), reaching antimicrobial activity up to 3200 AU/mL. The count of the strain MK1/3 was higher in yogurts from ewe goat milk (4.66 ± 0.30 CFU/g, log 10), in comparison with its count in yogurts from ewe milk (4.10 ± 0.10 CFU/g, log 10), with no influencing yogurt pH. Its use in 100% starter culture to process fresh cheese based on goat milk was revealed in the standard cheese quality with sufficient amount of lactic acid microbiota. To support the benefit of the strain MK1/3, additional human trials have been reinforced.